Pesticide Residues Analysis in Ambient Air (Revista Brasileira Multidisciplinar, 2009)
Identifying the distribution and levels of pesticides in ambient air can contribute to a better knowledge of the risk associated with these compounds to human health. Taking into account the necessity of efficiently measuring pesticides in this matrix, this article briefly discusses the methods employed, including both active and passive air sampling, pesticides analysis, as well as the procedures that have been implemented for method validation. Although analytical efforts to obtain reliable results have been demonstrated in the literature, further attempts are required to improve the sampling procedures and analytical methods for determining pesticides in ambient air.
Keywords: Pesticides; Ambient Air; Sampling and Analysis Procedures.